Polymorphisms of XRCC3 and XRCC7 and Colorectal Cancer Risk in Khorasan Razavi Province, Iran - Mehrzad, Jamshid (Asian Pac J Cancer Prev, 2019)
BACKGROUND: Colorectal cancer (CRC) is highly prevalent cancer, which should be genetically studied among different peoples of the world. OBJECTIVE: The aim of this study was to evaluate the effect of XRCC3T241M, XRCC3 A17893G and, for the first time, XRCC7 I3434T polymorphisms on CRC risk in Khorasan Razavi Province, Iran. MATERIALS AND METHODS: In this case-control study, 180 patients with CRC and 160 sex- and age-matched healthy controls were studied. Genotypes were determined by RFLP-PCR and ARMS-PCR. RESULTS: The incidence of CRC was observed to be significantly more in a heterozygous XRCC3 C/T genotype than in the CC genotype (OR 2.210, 95% CI 1.073-4.548, p=0.030). In the case of the XRCC7 I3434T polymorphism, CRC risk was significantly (4.3 fold) higher in I/T+T/T variant subjects compared to the I/I genotype (OR 4.394, 95% CI 2.721-7.096, p=0.000). Moreover, the XRCC3 A17893G polymorphism did not correlate with CRC. In addition, there was no significant difference between the distribution of genotypes of the three studied polymorphisms with demographic and clinicopathological features in the CRC patients. CONCLUSION: Polymorphisms of XRRC3 and XRCC7 genes are involved in CRC and should be considered as a risk factor.